Объяснение:
1) 7m(m³ – 8m² + 9) = 7m⁴ - 56m³ + 63m
2) (x – 2)(2x + 3) = 2x² - 4x + 3x - 6 = 2x² - x - 6
3) (3m – 4n)(5m + 8n) = 15m² - 20nm + 24nm - 32n² = 15m²+4nm-32n²
4) (y + 3)(y² + y – 6)=y³+3y²+y²+3y-6y-18=y³+4y²-3y-18
[tex]\displaystyle\bf\\1)\\\\7m(m^{3}-8m^{2} +9)=7m\cdot m^{3} -7m\cdot 8m^{2} +7m\cdot 9=\\\\=7m^{1+4} -56m^{1+2} +63m=7m^{5} -56m^{3} +63m\\\\\\2)\\\\(x-2)(2x+3)=x\cdot 2x+x\cdot 3-2\cdot 2x-2\cdot 3=\\\\=2x^{2} +3x-4x-6=2x^{2} -x-6\\\\\\3)\\\\(3m-4n)(5m+8n)=3m\cdot 5m+3m\cdot 8n-4n\cdot5m-4n\cdot 8n=\\\\=15m^{2} +24mn-20mn-32n^{2} =15m^{2} +4mn-32n^{2} \\\\\\4)[/tex]
[tex]\displaystyle\bf\\(y+3)(y^{2} +y-6)=y\cdot y^{2} +y\cdot y+y\cdot(-6)+3\cdot y^{2} +3\cdot y+3\cdot(-6)=\\\\=y^{3} +y^{2} -6y+3y^{2} +3y-18=y^{3} +4y^{2} -3y-18[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Объяснение:
1) 7m(m³ – 8m² + 9) = 7m⁴ - 56m³ + 63m
2) (x – 2)(2x + 3) = 2x² - 4x + 3x - 6 = 2x² - x - 6
3) (3m – 4n)(5m + 8n) = 15m² - 20nm + 24nm - 32n² = 15m²+4nm-32n²
4) (y + 3)(y² + y – 6)=y³+3y²+y²+3y-6y-18=y³+4y²-3y-18
Verified answer
[tex]\displaystyle\bf\\1)\\\\7m(m^{3}-8m^{2} +9)=7m\cdot m^{3} -7m\cdot 8m^{2} +7m\cdot 9=\\\\=7m^{1+4} -56m^{1+2} +63m=7m^{5} -56m^{3} +63m\\\\\\2)\\\\(x-2)(2x+3)=x\cdot 2x+x\cdot 3-2\cdot 2x-2\cdot 3=\\\\=2x^{2} +3x-4x-6=2x^{2} -x-6\\\\\\3)\\\\(3m-4n)(5m+8n)=3m\cdot 5m+3m\cdot 8n-4n\cdot5m-4n\cdot 8n=\\\\=15m^{2} +24mn-20mn-32n^{2} =15m^{2} +4mn-32n^{2} \\\\\\4)[/tex]
[tex]\displaystyle\bf\\(y+3)(y^{2} +y-6)=y\cdot y^{2} +y\cdot y+y\cdot(-6)+3\cdot y^{2} +3\cdot y+3\cdot(-6)=\\\\=y^{3} +y^{2} -6y+3y^{2} +3y-18=y^{3} +4y^{2} -3y-18[/tex]